2008
DOI: 10.1002/cjce.5450830210
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Dynamic Adsorption Behaviour of Ethyl Acetate from Air on 5A and 13X Molecular Sieves

Abstract: On a obtenu des données expérimentales pour l'adsorption de l'acétate d'éthyle présent dans l'air à l'aide de tamis moléculaires 5A et 13X, en faisant varier la concentration d'adsorbat et la vitesse d'entrée ainsi que le rapport entre le diamètre et la longueur de lit, afi n d'étudier leurs effets sur la performance du lit adsorbeur. Un modèle mathématique reposant sur l'approximation de la force motrice linéaire est validé avec les données expérimentales et simulé pour comprendre les effets d'autres paramètr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The model developed in the present study reasonably predicted the VOC concentration. The best fit was verified by root mean square error (ı) range from 0.02 to 0.07 [24]. It was observed that the equilibrium adsorption constant, K decreased drastically with the increase in temperature.…”
Section: Adsorption Capacities Of Adsorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model developed in the present study reasonably predicted the VOC concentration. The best fit was verified by root mean square error (ı) range from 0.02 to 0.07 [24]. It was observed that the equilibrium adsorption constant, K decreased drastically with the increase in temperature.…”
Section: Adsorption Capacities Of Adsorbentsmentioning
confidence: 99%
“…The column was divided into N equal increments ( z = 1/n) and the convergence was studied by increasing the value of n. The calculated breakthrough curves converge when n was greater than 35. The simulation was carried out until n equal to 200 to ensure that there was no error due to numerical resolution of the system [24]. The main purpose of the approach developed in this work is that the parameters appearing in the model can be easily estimated from the correlations.…”
Section: Breakthrough Curvesmentioning
confidence: 99%
“…Gaseous VOC breakthrough tests for molecular sieve adsorption have frequently been utilized to evaluate the equilibrium adsorption capacity (Q e , g VOC/g MS) (Yoo, et al, 2005;Lin, et al, 2005;Manjare and Ghoshal, 2005). Breakthrough tests of MEK adsorption (C = 1448 (1471 ± 319) and 440 (483 ± 183) ppm) were performed herein to verify the feasibility of the simulated equilibrium capacity data in Table 3.…”
Section: Breakthrough Experiments Of Mek Adsorption By Molecular Sievementioning
confidence: 99%
“…This indicates the overall drop in the adsorption rate at higher flow rate [4,13]. A more detailed analysis has revealed that the heat of adsorption varies strongly with VOC concentration range [12]. However, vent streams with high VOC concentration can be diluted with air or inert gases.…”
Section: Introductionmentioning
confidence: 98%
“…Due to their unique pore system and high surface area, these materials are actively investigated for adsorption of organics from air/gas [10,11]. More hydrophobic zeolites (usually those with high Si/Al ratios) are receiving attention due to their relatively high thermal stability while showing higher affinity towards VOC adsorption in humid conditions [4,9,12].…”
Section: Introductionmentioning
confidence: 99%